Personality traits and gender effect on athletes and non-athletes selfhandicapping strategies over time - Nikola Prpa (University of Novi Sad, Faculty of Sport and Physical Education, 2017)
The aim of this research was to examine differences in the use of self-handicapping strategies in athletes and non-athletes, changes in self-handicapping strategies that can occur with the approach of an important event, and the relationships between these strategies and personality traits, gender, and some external criteria such as performance. The sample included 183 subjects (mean age 21.16 years) consisting of 102 non-athletes and 81 athletes. Three questionnaires were used: VP+2, for measuring personality dimensions of seven-factor model, SH-17, for the assessment of changes in the use of self-handicapping strategies through time and a general biographical questionnaire. A general linear model for repeated measures was used for data analysis. Significant correlation was found between self-handicapping strategies and the number of medals and awards won at international and domestic competitions. The results also showed a positive correlation between self-handicapping strategies and dimensions of Neuroticism and Extraversion and negative with Conscientiousness. Also, a statistically significant difference in the use of self-handicapping strategies was found between athletes and non-athletes, showing that non-athletes express more self-handicapping behaviour. The results indicate that the frequency of selfhandicapping behaviour does not change through time. The effect of gender on self-handicapping is not significant, but there was a statistically significant interaction effect of gender and population on self-handicapping behaviour. It indicates that male non-athletes are more prone to self-handicapping 10 days before an important competition (exam or public speaking for general population, or "game of the season" for sporting population) compared to male athletes. These results, apart from the gender differences, are consistent with the results of previous studies. Limitations of this research and possible directions for future studies were also considered.